Analysis Of Electric Propulsion Performance On Submersible 60 M With Motor Dc 2x1850 Kw 380 V Using Ohmformer At Voltage 190 Vdc 10260 Ah And Without Using Ohmformer At Voltage 115 Vdc 10260 Ah - Sardono Sarwito; Muhammad Agus Sulaiman (International Journal of Marine Engineering Innovation and Research, 2018)
Electric propulsion system is ship propulsion system using electric motor to replace performance of main engine. Submersible ships use DC motor as electric propulsion system because DC motor has advantages of speed control and lower propulsion noise when submersible ship is at submerge condition. Design of electric propulsion system is using two DC motor that are connected in series. Battery and generator as its power supply. Designs of electric propulsion system that will be reviewed here are using ohmformer and without using ohmformer. Those designs will be simulated using MATLAB Simulink. The results of the simulation are that the design using ohmformer is greater in speed and power than without using ohmformer. Because of using ohmformer can control input voltage of DC motor that use generator as its power supply. Meanwhile, ohmformer-less design has constant input voltage that use battery as its power supply. Next, design of using ohmformer can be used for silent run (low speed), sailing run (medium speed) and quick run (high speed). Then design of without using ohmformer can be used for sailing run (medium speed).